STUDENTS’ PERCEPTION TOWARDS TEACHERS’ CHARACTERISTIC PERCEIVED BY STUDENTS OF ENGLISH DEPARTMENT AT MUHAMMADIYAH UNIVERSITY OF NORTH MALUKU - Erwin Gay; Jusmin HJ Wahid; Achmad Fajri Sulaiman (JURNAL DODOTO, 2021)
Every human has a different perception. Perception is a response that is issued based on what a person experiences. This study aims to know the students’ perception towards teachers’ characteristic particularly in English Department at Muhammadiyah University of North Maluku. There are three characters discussed in this study: professional teacher character, unprofessional teacher character and expected character. This is a descriptive qualitative study. Research subject is the English Department Students at Muhammadiyah University of North Maluku. The instruments of data collection used are questionnaire and interviews. Research shows that each student has their own perception of thhe teacher’s characteristics in this professional teacher character, unprofessional teacher character and expected character. Professional teacher character according to student perception are consistent with the appointed times, objective to assessment, nice in approach to the students, be able to make the classroom atmosphere more comfortable, better at learning materials, and able to adapt anywhere. Meanwhile, unprofessional teacher character according to student perception are unfair in assessment, ignore the students, just focus on one student, lack of approach to students, inconsistent with time, and rare to explain the material. Students are expecting a teacher character who does not focus only on one student, able to cultivate the classroom, humble, got a sense of responsibility as a teacher to teach, be a good example, and honest and intelligent. Keywords: Students’ Perception, Teachers’ Characteristic, Professional, Unprofessional